Low-grade cribriform cystadenocarcinoma of the palatal gland: A case report - KOKABU, SHOICHIRO (Oncol Lett, 2015)
Low-grade cribriform cystadenocarcinoma (LGCCC) is a malignant salivary gland tumor. LGCCC occurs rarely, with the parotid gland being the most commonly afflicted site. Few cases arise in other sites. The present study reports a case of LGCCC that occurred at the palatal gland of the hard palate. A 56-year-old female was referred to Saitama Medical University Hospital (Moroyama, Saitama, Japan) due to an intraoral mass. Since cytological examination and biopsy led to a diagnosis favoring a neoplasm, but with uncertain malignant potential, the tumor was resected with a safe surgical margin. The specimen was thoroughly examined. Microscopically, there was a well-demarcated, unilocular cyst with the lumen lined by tumor cells. The tumor cells were arranged in tubular, cribriform and solid structures in the area of the intracystic mass lesions. Nuclear atypia was inconspicuous, although mitotic figures were observed throughout the tumor. Neither local nor perineural invasion was present. On immunohistochemistry, the tumor cells were diffusely positive for S-100 protein. Myoepithelial markers, calponin and p63, highlighted the cells rimming the cystic mass. The final histopathological diagnosis was of LGCCC. The tumor was completely resected. At 1 year post-resection, the patient exhibited no recurrence or distant metastasis. LGCCC is regarded as clinically indolent. However, there is little literature available to aid with prognosis prediction due to the rarity of LGCCC cases. Thus, greater experience and longer follow-up periods are necessary to find the optimal/curative treatment for patients with LGCCC and to clarify the pathophysiology.